2001
DOI: 10.1023/a:1007851413867
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in symptoms of posttraumatic stress: Does culture play a role?

Abstract: Ifgender differences in posttraumatic stress disorderfollowfrom culturally-defined mles and rules, they should be greater in societies that foster traditional views of masculinity and femininity than in societies that adhere to these traditions less rigidly. Data were collected 6 months after Hurricanes Paulina (Acapulco; N = 200) and Andrew (Miami; White n = 135; Black n = 135). In regression analyses predicting scores on the Revised Civilian Mississippi Scale, Sex x Cultural Group interactions emerged for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
116
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 27 publications
9
116
1
2
Order By: Relevance
“…Specifically, research suggests that women may be more likely to experience greater PTSD because of acute biological responses (Felmingham et al, 2012), greater appraisals of threat (Mak et al, 2004), or distinct coping styles (Norris et al, 2001). Interestingly, and in contrast with much evidence that women are more at risk of depression (Kessler et al, 1993), men and women reported comparable levels of depression in the current study.…”
Section: Discussioncontrasting
confidence: 66%
“…Specifically, research suggests that women may be more likely to experience greater PTSD because of acute biological responses (Felmingham et al, 2012), greater appraisals of threat (Mak et al, 2004), or distinct coping styles (Norris et al, 2001). Interestingly, and in contrast with much evidence that women are more at risk of depression (Kessler et al, 1993), men and women reported comparable levels of depression in the current study.…”
Section: Discussioncontrasting
confidence: 66%
“…The results of a methodologically sound intercultural study support this notion [Norris et al, 2001]. The authors compared stress reactions after hurricanes in three culturally different samples: Mexicans, African Americans, and Anglo-Americans.…”
Section: Methodological Issuesmentioning
confidence: 69%
“…The majority of the sample was female and Caucasian, precluding invariance testing of confirmatory models across gender and ethnicity. In light of recent data which suggest that cultural influences interact with gender differences in PTSD symptomatology (e.g., Norris, Perilla, Ibanez, & Murphy, 2001), future work should examine whether the IES-R factor structure is invariant across culture and gender. This research direction is facilitated by the presence of translated versions of the scale (e.g., Asukai et al, 2002, Baguena et al, 2001, Wu & Chen, 2003.…”
Section: Discussionmentioning
confidence: 99%